The Current State and Ways to Increase the Real Income of the Population of Kazakhstan - N. N. Zhanakova; G. Bodauhan; G. Z. Nigmetova; D. D. Mangibayeva; L. G. Kirbasova (Экономика: стратегия и практика)
The purpose of the article is to study the influence of factors on the real incomes of the population of Kazakhstan and substantiate priority ways to increase them. Using a factor-correlation analysis of the real monetary income of the population with indicators of nominal monetary income, inflation, and the growth rate of the country's economy, the influence of these indicators on the growth rate of income of the population was revealed. Data from the Bureau of National Statistics from 2010 to 2022 were used. The increase in the minimum wage is recognized as one of the tools for increasing incomes, which will lead to an increase in GDP by demand, and will lead to an increase in the IFO of GDP by demand by 0.24%, provided that real household spending increases by 1%. An increase in household incomes will lead to an increase in demand for consumer goods and services, which will lead to an increase in food prices by 0.14%, provided that real household spending increases by 1%. For the growth of real incomes of the population, it is important to strengthen the business activity of the society. An increase in the contribution of SMEs by 1% will lead to an increase in household incomes by 0.32%. An increase in lending to the economy by 1% will lead to an increase in household incomes by 0.11%. The growth of non-primary exports by 1% will lead to an increase in household incomes by 0.13%.